Effective pedagogy as a key factor in the educational process - Shohistakhon Akmaljon qizi Khoshimjonova; Oyshabegim Kamardinova; Scientific advisor: Mahliyo Mirzakarimova (Science and Education, 2025)
This article analyzes the main principles, methods and advantages of effective pedagogy in the modern education system. The effective interaction between the teacher and the student, approaches adapted to the individual abilities of students, the role of innovative technologies in the educational process are highlighted. The article considers effective pedagogy not only as a means of imparting knowledge, but also as a key factor in the educational process.